Audit Energi Di Kantor Walikota Manado, Sulawesi Utara - Afyudin M. Umanailo; Meita Rumbayan; Vecky C. Poekoel (Jurnal Teknik Elektro dan Komputer, 2018)
Abstrak-Consumption of electric energy continues to increase, with the increase in electrical energy needs, the reliability of a power system must also be directly proportional to the needs of electrical energy. Energy Audit is a method used to calculate the amount of energy consumption in buildings and recognize ways to save.The Energy Audit at the Manado Mayor's office, North Sulawesi, aims to determine the energy usage and energy utilization conditions and energy savings opportunities in the mayor's office of Manado, North Sulawesi.From the data obtained there are some buildings / rooms that have not been fulfilled and there is one room that meets the criteria of Enegi Audit. And from this analysis is used planning to optimize the use of electric energy and other energy utilization in the office of mayor of Manado, North Sulawesi to be more economical and support Manado city program to Manado Smart City . Keywords: Electrical Energy, Energy Audit, Manado Mayor's office, Smart City  Abstrak-Konsumsi akan energi listrik terus meningkat, dengan peningkatan kebutuhan energi listrik maka keandalan suatu sistem tenaga listrik juga harus berbanding lurus dengan kebutuhan energi listrik. Audit Energi adalah metode yang dipakai untuk menghitung besarnya konsumsi energi pada bangunan gedung dan mengenali cara – cara untuk penghematannya. Audit Energi di kantor Walikota Manado, Sulawesi Utara bertujuan untuk mengetahui penggunaan energi dan  Kondisi pemanfaatan energi serta peluang penghematan energi di kantor walikota Manado, Sulawesi Utara. Dari data yang diperoleh ada beberapa bagunan/ruangan yang belum memenuhi  dan ada satu ruangan yang memenuhi kriteria dari Audit Enegi. Dan dari Analisa ini digunakan perencanaan untuk mengoptimalkan penggunaan  energi listrik serta pemanfaatan energi lain di kantor walikota Manado, Sulawesi Utara agar dapat lebih ekonomis dan mendukung program kota Manado menuju Manado Smart City . Kata Kunci : Audit Energi, Energi Listrik, kantor Walikota Manado, Smart City